Đieu lệ tạm thơi vè chẽ đợ hợp đơng kinh tẽ (Vietnamese law coll. (Harvard Law School), 1963)
Decisions, implementation, and instructions on organizational matters relating to economic contracts, sale, payment, transportation, construction, and bidding.